The Information Needs and Media of Small Islands Society - Yoganingrum, Ambar; Hantoro, Wahyoe S (KOMUNITAS: INTERNATIONAL JOURNAL OF INDONESIAN SOCIETY AND CULTURE, 2015)
The purpose of the study is to identify the needs and appropriate media for information services regarding the management of freshwater and sanitation of small island community in North Lombok. The data was collected using a questionnaire with the households as respondents. The study then compared two samples i.e. the community in the district of Lombok north and Kepulauan Seribu using Kolmogorov-Smirnov technique. The community in both districts has similarities and differences in the aspect of demographic, understanding, behaviors as well as the information needs and the preferred media. The study concludes that the community in Lombok Utara needs information about global warming and its effect to the damage of freshwater and sanitation. The media information such as film animation is necessary to be considered due to fact that people of the two districts have a longer time on the land.